Potential of jute fiber-reinforced composites in the manufacture of components and equipment used on ships and hulls - Dinh Tuyen Nguyen; Huu Cuong Le (Journal of Emerging Science and Engineering, 2023)
In today's maritime field, metal materials are very popular, but they have certain limitations. To meet a variety of requirements, many new materials have been used, including fiberglass reinforced composites, but these materials are often difficult to decompose, have poor recyclability, and cause a great impact on the environment after a period of use. There have been many studies aimed at using natural fibers to replace glass fibers in order to solve the limitations of glass fiber reinforced composites. Jute is one of the most popular natural fibers. Recently, researchers have focused their attention on jute fiber-reinforced composites. This article will talk about the potential of jute fiber reinforced composites applied to the manufacture of components and equipment used on ships and hulls.